CREDIT CHAINS AND MORTGAGE CRISES - Verme, Paula Lourdes Hernandez (European Scientific Journal, ESJ, 2013)
I examine a production economy with a financial sector that contains multiple layers of credit. Such layers are designed to constitute credit chains which are inclusive of a simple mortgage market. The focus is on the nature and contagion properties of credit chains in an economy where the financial sector plays a real allocative role and agents have a nontrivial choice of whether to default on mortgages or not. Multiple equilibria with different rates of default are observed, due to the presence of strategic complementarities. Default can trigger a financial crisis as well as constrain the purchases of factors of production, thus leading to potentially serious effects on real activity.